2019
DOI: 10.3390/app9081690
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Revisited: An Analytic Quantum Approach

Abstract: We address the second-harmonic generation process in a quantum frame. Starting with a perturbative approach, we show that it is possible to achieve a number of analytic results, ranging from the up-conversion probability to the statistical properties of the generated light. In particular, the moments and the correlations of the photon-number distribution of the second-harmonic light generated by any initial state are retrieved. When possible, a comparison with the results achieved with the classical regime is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The arguments covered in the previous section are then developed in the research articles, which consist of eight papers, offering a panorama of the present studies in quantum optics and analyzing some specific issues of the different lines of research in which this field is structured. In summary, issues concerning non-locality studies range from the application of the de Broglie-Bohm model to Gauss-Maxwell beams [13] to revisiting complementarity relations in bipartite quantum systems [14]; correlations in atoms are investigated in [15,16], photon emission and statistics in [17,18] and methods in quantum technologies in [19,20] The first paper [13] of this section deals with a Bohmian-based approach to Gauss-Maxwell beams, a particularly appropriate and natural tool in optical problems dealing with Gaussian beams acted or manipulated by polarizers: a hydrodynamic-type extension of such a formulation is provided and discussed, complementing the notion of the electromagnetic field with that of (electromagnetic) flow or streamline. The described features confer the approach a potential interest in the analysis and description of single-photon experiments.…”
Section: Quantum Optics For Fundamental Quantum Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arguments covered in the previous section are then developed in the research articles, which consist of eight papers, offering a panorama of the present studies in quantum optics and analyzing some specific issues of the different lines of research in which this field is structured. In summary, issues concerning non-locality studies range from the application of the de Broglie-Bohm model to Gauss-Maxwell beams [13] to revisiting complementarity relations in bipartite quantum systems [14]; correlations in atoms are investigated in [15,16], photon emission and statistics in [17,18] and methods in quantum technologies in [19,20] The first paper [13] of this section deals with a Bohmian-based approach to Gauss-Maxwell beams, a particularly appropriate and natural tool in optical problems dealing with Gaussian beams acted or manipulated by polarizers: a hydrodynamic-type extension of such a formulation is provided and discussed, complementing the notion of the electromagnetic field with that of (electromagnetic) flow or streamline. The described features confer the approach a potential interest in the analysis and description of single-photon experiments.…”
Section: Quantum Optics For Fundamental Quantum Mechanicsmentioning
confidence: 99%
“…The arguments of [17,18] concern photon emission and statistics. The high-frequency electromagnetic emission from non-local wavefunctions is analyzed in [17], where it is shown that, in systems with non-local potentials or other kinds of non-locality, the Landauer-Büttiker formula of quantum transport leads to replacing the usual gauge-invariant current density J with a current J ext , which has a non-local part and coincides with the current of the extended Aharonov-Bohm electrodynamics.…”
Section: Quantum Optics For Fundamental Quantum Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, classical radiation fields are used, which is appropriate in the strong field limit. However, highly interesting effects in SHG (and fluorescence in general) appear in the low photon regime [20][21][22][23], where quantum effects generally dominate [24] and the so-called rotating wave approximation (RWA) [25][26][27][28][29] may be inadequate [30][31][32].…”
Section: Introductionmentioning
confidence: 99%